Revitalizing Incident Commander Leadership: Breakthroughs Through Weighting Methods at Airport Emergencies - Abdullah, Anton; Komalasari, Yeti; Danim, Sudarwan (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study explores the use of a Decision Support System (DSS) to enhance Incident Commander (IC) leadership in airport emergency scenarios. Effective IC leadership is crucial in airport emergency management, requiring a diverse skill set. We investigate competencies related to command, operations, planning, logistics, administration, and customer service. Using a mixed-methods approach, we conducted a descriptive case study at Palembang Aviation Polytechnic. Primary data, including observations, interviews, and questionnaires, along with secondary data from internal documents, guided our research. Purposive sampling selected participants from faculty, Diploma Three Program trainees, and airport practitioners. Our findings highlight customer service as a leading criterion, followed by others, with logistics criteria being essential. This study contributes novel insights to airport emergency management by enhancing IC proficiency and emphasizing interconnected emergency management facets. It underscores the ethical imperative of IC leadership development, promoting safety and effectiveness in airport emergency response services.